Program Mindfulness for Prisoners (Mindfulners) untuk Menurunkan Depresi pada Narapidana - Resa Wuryansari; Subandi Subandi (Faculty of Psychology, Universitas Gadjah Mada, 2019)
Condition of the prison which is very different from the outside world gives rise to many stressors for inmates living in it. It makes the inmates have a high risk to suffer from any psychological problems. One of the most common psychological problems is depression. Mindfulness for Prisoners (Mindfulners) was developed from Mindfulness Based Cognitive Therapy (MBCT) which is a form of mindfulness therapy based on cognitive-behavioral approach. The purpose of this study was to examine the effectiveness of Mindfulners in reducing depression symtomps in inmates living in prisoner. The mindfulners program was conducted in the form of group therapy with the criteria of participants is inmates with more than 1 year sentence and has a BDI-II score in the medium to high category.The mindfulners program be held in 4 meetings, included 8 sessions with a duration of 120-150 minutes. This research used one group pretest-posttest design. Subject also given follow up after one week from the time of posttest. Quantitative data analysis technique using the paired sample t-test against pretest and posttest scores on the depression scale and mindfulness scale as a manipulation check. The result showed Z = -2.207b (p < 0.05). This suggest that Mindfulners Program can reduce depression in inmates living in prisoner significantly.